2020
DOI: 10.1186/s13244-019-0795-6
|View full text |Cite
|
Sign up to set email alerts
|

Combining molecular and imaging metrics in cancer: radiogenomics

Abstract: Background: Radiogenomics is the extension of radiomics through the combination of genetic and radiomic data. Because genetic testing remains expensive, invasive, and time-consuming, and thus unavailable for all patients, radiogenomics may play an important role in providing accurate imaging surrogates which are correlated with genetic expression, thereby serving as a substitute for genetic testing. Main body: In this article, we define the meaning of radiogenomics and the difference between radiomics and radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
142
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(143 citation statements)
references
References 150 publications
(123 reference statements)
1
142
0
Order By: Relevance
“…Similar radiogenomic associations have also been reported for other cancer types and imaging modalities such as MRI (glioblastoma [57,58], oligodendrogliomas [59] and breast cancer [60,61]), CT (lung cancer [62], lung adenocarcinoma [63] and hepatocellular carcinoma [64]) and PET (non-small cell lung cancer [65,66] and lymphoma [67]). Several reviews have already comprehensively compared these radiogenomic studies and their main limitations [68,69].…”
Section: Main Textsupporting
confidence: 75%
“…Similar radiogenomic associations have also been reported for other cancer types and imaging modalities such as MRI (glioblastoma [57,58], oligodendrogliomas [59] and breast cancer [60,61]), CT (lung cancer [62], lung adenocarcinoma [63] and hepatocellular carcinoma [64]) and PET (non-small cell lung cancer [65,66] and lymphoma [67]). Several reviews have already comprehensively compared these radiogenomic studies and their main limitations [68,69].…”
Section: Main Textsupporting
confidence: 75%
“…This method uses high-throughput extraction of large numbers of quantitative radiomics features obtained from medical images using advanced mathematical algorithms to determine tumor phenotypes [ 17 , 18 , 19 ]. Thus, the heterogeneity of the entire tumor volume is assessed compared to biopsies that assess the heterogeneity in a small portion of the tumor and at a single anatomical site [ 20 , 21 , 22 , 23 , 24 ]. Several previous studies [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] have shown that radiomics features based on multiphasic multidetector computed tomography (MDCT) images perform efficiently in differentiating between high-/low-grade ccRCC tumors.…”
Section: Introductionmentioning
confidence: 99%
“…As it has been observed by many authorities psychometric analysis is an effective tools in in deciding what number of options, keeping questions in bank and comparing students achievement. [ 23 ] Amani et. al.…”
Section: Introductionmentioning
confidence: 99%
“…(2020) used psychometric analysis to compare quality of MCQs designed by residents in radiology program and that design by teacher. [ 23 ] To ensure fair response from the examinees, many factors should be considered: on the top of these factors is the reliability of the questions and the test, the quality of the questions, the validity of the test and finally the language back ground of the examinee. Psychometric analysis will provide some answers to these questions by tell us how many option is needed for those who uses English as second language and can alert us to possible areas for improvement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation